2019
DOI: 10.3390/atmos10120750
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate of Gravity Wave Amplitudes Observed in Sodium Lidar Density Profiles and Nightglow Image Data

Abstract: Amplitude growth rates of quasi-monochromatic gravity waves were estimated and compared from multiple instrument measurements carried out in Brazil. Gravity wave parameters, such as the wave amplitude and growth rate in distinct altitudes, were derived from sodium lidar density and nightglow all-sky images. Lidar observations were carried out in São Jose dos Campos (23 ∘ S, 46 ∘ W) from 1994 to 2004, while all-sky imagery of multiple airglow layers was conducted in Cachoeira Paulista (23 ∘ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Ern et al (2011) shows absolute F M values of ∼ 10 −3.9 Pa at 50 km altitude and ∼ 10 −4.3 Pa at 70 km altitude in the Northern Hemisphere in January for latitudes/longitudes near the Kühlungsborn observatory, evidencing momentum flux deposition in the middle atmosphere. Thus, it is likely that the small-scale waves observed here mostly dissipate as they travel through the MLT, in agreement with Vargas et al (2019). In another flux estimation study using airglow imagery of gravity waves, Vargas et al (2009) revealed F M ranging from ∼ 1.5 to ∼ 4.5 m 2 s −2 , while radar measurements of, e.g, Yuan and Fritts (1989) estimated F M = 5-15 m 2 s −2 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Ern et al (2011) shows absolute F M values of ∼ 10 −3.9 Pa at 50 km altitude and ∼ 10 −4.3 Pa at 70 km altitude in the Northern Hemisphere in January for latitudes/longitudes near the Kühlungsborn observatory, evidencing momentum flux deposition in the middle atmosphere. Thus, it is likely that the small-scale waves observed here mostly dissipate as they travel through the MLT, in agreement with Vargas et al (2019). In another flux estimation study using airglow imagery of gravity waves, Vargas et al (2009) revealed F M ranging from ∼ 1.5 to ∼ 4.5 m 2 s −2 , while radar measurements of, e.g, Yuan and Fritts (1989) estimated F M = 5-15 m 2 s −2 .…”
Section: Discussionsupporting
confidence: 79%
“…According to Vargas et al (2019), only a minority of waves seen in the airglow (∼ 5 %) are in non-dissipating regimes. Vargas et al (2019) also show that the majority of the gravity waves present strong dissipation and transfer momentum flux to the main flow within a distance of two atmospherescale heights (12-14 km). Thus, the large F M waves discussed here are likely to present dissipative or breaking characteristics given their larger amplitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equatorial E region is also the part of the Mesosphere-Lower-Thermosphere (MLT) region of the atmosphere that hosts robust wave activities and sporadic E layer activities from the tidal wave modes and gravity wave modes [19][20][21]. The radar observations reveal FAI-E with periodic-EDs from these modes before the occurrence of EPBs [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that averages of wind be used in short-day intervals for difficult airglow observational conditions and that hourly winds be used for analyses of specific wave filtering. Vargas et al [6] presented their analysis of AGW observations made by a Na lidar and an all-sky imager in the Brazilian sector. Amplitude growth rates of gravity waves were estimated and compared from multiple instrument measurements.…”
mentioning
confidence: 99%